EU Fiscal Governance Reforms: A Perspective of Independent Fiscal Institutions - Sebastian Barnes (Intereconomics, 2022)
The fiscal framework needs in practice to achieve a balance between, on the one hand, effective budgetary rules that allow governments to commit to sound policies and, on the other, judgements and discretion in how these are applied so that the framework adequately reflects the complexity of the situations that countries may find themselves in.
Keywords: E62; H61; H77; 330; Finanzreform; EU-Staaten